Australia and New Zealand Transplant and Cellular Therapies COVID‐19 vaccination consensus position statement. Issue 8 (22nd August 2021) - Hamad, Nada; Ananda‐Rajah, Michelle; Gilroy, Nicole; MacIntyre, Raina; Gottlieb, David; Ritchie, David; Harrison, Simon; Kennedy, Glen; Watson, Anne M.; Greenwood, Matthew; Doocey, Richard; Perera, Travis; et al.
Abstract: Australia and New Zealand have achieved excellent community control of COVID‐19 infection. In light of the imminent COVID‐19 vaccination roll out in both countries, representatives of all adult and paediatric allogeneic bone marrow transplant and cellular therapy (TCT) centres as well as representatives from autologous transplant only centres in Australia and New Zealand collaborated with infectious diseases specialists with expertise in TCT on this consensus position statement regarding COVID‐19 vaccination in TCT patients in Australia and New Zealand. It is our recommendation that TCT patients, should have expedited access to high‐efficacy COVID‐19 vaccines given that these patients are at high risk of morbidity and mortality from COVID‐19 infection. We also recommend prioritising vaccination of TCT healthcare workers and household members of TCT patients. Vaccination should not replace other public health measures in TCT patients given the effectiveness of COVID‐19 vaccination in TCT patients is unknown. Furthermore, given the limited available data, prospective collection of safety and efficacy data of COVID‐19 vaccination in this patient group is a priority.